The Influence of Salary Compensation, Leadership Communication, Work Culture, Competence, and Motivation on The Work Productivity of Generation Z In Culinary MSMES In Balikpapan - Ferinda, Yosica; Krisprimandoyo, Denpharanto Agung; Christiani, Natalia (Journal Research of Social Science, Economics, and Management, 2025)
This study analyzes the effect of salary compensation, leadership communication, work culture, competence, and motivation on the work productivity of Generation Z in culinary MSMEs in Balikpapan, using multiple linear regression with 135 respondents. The study reveals that Generation Z is a workforce group with unique characteristics that require an adaptive and innovative management approach. The results show that competence has a positive and significant effect (B=0.348; p<0.05), while salary compensation (B=-0.117; p<0.05) and leadership communication (B=-0.242; p<0.05) have significant negative effects. Work culture and motivation are not significant partially, but simultaneously, all variables have a significant effect. These findings provide practical recommendations for MSMEs to optimize competency development, revise compensation schemes, and improve leadership communication to suit the characteristics of Gen Z.